Penentuan Nilai Ekivalen Kendaraan Ringan (Ekr) Untuk Kendaraan Becak Motor (Bentor) Pada Ruas Jalan Arif Rahman Hakim dan Jalan Manggis Kota Gorontalo - Fitriyanti Ui; Yuliyanti Kadir; Marike Mahmud (Journal of Applied Civil and Environmental Engineering, 2021)
The equivalent value of light vehicles (elv) is influenced by the size and speed of the vehicle, the greater the vehicle the equivalent value of light vehicles (elv) the higher, the higher the vehicle speed the equivalent value of light vehicles (elv) will be lower. The purpose of this study is to determine the equivalent value of light vehicles (elv) for motor tricycles vehicle (mtv) as part of the traffic and the performance of the Arif Rahman Hakim Road and Gorontalo City Manggis Road. The location of the study was conducted on Jalan Arif Rahman Hakim and Manggis Street. Primary data collected is data of traffic flow volume. The analysis was carried out using the simple linear regression analysis method and the 2014 Indonesian road capacity guidelines. From the calculation results obtained an equivalent value of light vehicles (elv) for motor Â tricycles vehicle (mtv) on the Arif Rahman Hakim Road section of 0.55 and on the Manggis Road section obtained an equivalent value of light vehicles (elv) of 0.46. Then do the calculations to analyze the performance of the Arif Rahman Hakim and Manggis Roads obtained the degree of saturation (DS) <0.85. The DS scores show that both locations are very suitable to serve the flow of traffic during peak hours.Keywordsâ€”elv, motor tricycles vehicle , linear regression, road performance